A radiological study of ossification at the lower end of humerus for age estimation among boys in Central Karnataka, India - Choudhary, Umesh; Kumar, Saroj; Singh, Anand; Bharti, Priyanka (International Journal of Research in Medical Sciences, 2017)
Background: The earlier studies which were conducted across the world on long bones to know the age reveal that there is no uniform sequence for the epiphyseal union of long bones in different countries or different places in the same country. To ascertain this in Central Karnataka, India present study was done. Methods: A radiological study of lower end of Humerus was conducted on total 100 boys of age group 11–20 years from different schools and colleges of Chitradurga district of central Karnataka, India. The radiographs were studied in detail and the findings were recorded. Results: Fusion of epiphyseal centre of lateral epicondyle with that of Capitulum was seen between 12–15 years. Fusion of epiphyseal centre of Capitulum with that of Trochlea was seen between 12–15 years. Fusion of conjoint epiphysis with the shaft was seen between 12–16 years. Fusion of epiphyseal centre of medial epicondyle with shaft was seen between 14-17 years. Conclusions: In general, fusion of epiphysis occurs around 12-17 years.